Iron Polymaltose Infusion Effects on Bone Scintigraphy and Remodeling. (27th October 2022) - Kang, Christine; Jiang, James Y.; Wong, Veronica; Man, Jennifer; Mansberg, Robert
Abstract: A 73-year-old woman with metastatic breast cancer and known widespread skeletal metastases was referred for bone scintigraphy. Delayed images acquired at 2 and 5 hours postinjection of 30 mCi (1089 MBq) 99m Tc-HDP demonstrated markedly reduced bony uptake, markedly increased renal activity, and significantly increased soft tissue accumulation. By contrast, appropriate skeletal uptake of 99m Tc-HDP was seen in prior bone scans. The patient had been treated for iron deficiency anemia with an infusion of 1 g of iron polymaltose approximately 22 hours before injection of 99m Tc-HDP. This phenomenon may be due to transient reduced bone resorption with increased FGF23 release secondary to IV iron supplementation.